2018
DOI: 10.1177/2325967118760854
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Return-to-Play Times: A Broader Perspective on Concussion Recovery

Abstract: Background:Return-to-play protocols describe stepwise, graduated recoveries for safe return from concussion; however, studies that comprehensively track return-to-play time are expensive to administer and heavily sampled from elite male contact-sport athletes.Purpose:To retrospectively assess probable recovery time for collegiate patients to return to play after concussion, especially for understudied populations, such as women and nonelite athletes.Study Design:Cohort study; Level of evidence, 3.Methods:Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…Increased postconcussion symptoms and longer recovery time in females compared with males have been well documented. 8,[12][13][14] Although direct comparisons with these results are difficult due to differences in recovery criteria, the target age group, and the study design, our results provide additional evidence to support the existence of sex differences in concussion recovery timelines. Zuckerman et al 15 analyzed age groups similar to those in our investigation and reported that females took approximately 2 days longer to return to their baseline total symptom score, which directly agreed with our findings.…”
Section: Effect Of Sexmentioning
confidence: 57%
See 1 more Smart Citation
“…Increased postconcussion symptoms and longer recovery time in females compared with males have been well documented. 8,[12][13][14] Although direct comparisons with these results are difficult due to differences in recovery criteria, the target age group, and the study design, our results provide additional evidence to support the existence of sex differences in concussion recovery timelines. Zuckerman et al 15 analyzed age groups similar to those in our investigation and reported that females took approximately 2 days longer to return to their baseline total symptom score, which directly agreed with our findings.…”
Section: Effect Of Sexmentioning
confidence: 57%
“…The 12-(n ¼ 2), 13-(n ¼ 18), and 18-(n ¼ 25) year age groups were excluded from the interaction analysis due to inadequate sample sizes. A 2-way ANOVA indicated main effects of sex (P ¼ .048) and age (P ¼ .013), with no interactions (P ¼ .36) between sex and age (14,15,16, and 17 years).…”
Section: Resultsmentioning
confidence: 98%
“…Return-to-play timelines in USAFA cadets (mean time of 29.4 days) have also exceeded the commonly cited recovery window of 10 to 14 days (34,35). Similar to the findings of O'Connor et al (33), male (24.7 days) and collegiate athlete-cadets (25.4 days) returned quicker than did female (35.5 days) and non-intercollegiate (34.7 days) cadets (34). In summary, this collection of publications represents the first set of normative values for an underrepresented military population and begins the initial phases of comprehending concussion risk, reporting, and recovery patterns in Service Academy cadets and military service members.…”
Section: Service Academy Specific Findings To Datementioning
confidence: 87%
“…However, acute symptom burden was the most consistent and robust predictor of recovery time with endorsement of more than 11 symptoms, indicating longer recovery periods (33). Return-to-play timelines in USAFA cadets (mean time of 29.4 days) have also exceeded the commonly cited recovery window of 10 to 14 days (34,35). Similar to the findings of O'Connor et al (33), male (24.7 days) and collegiate athlete-cadets (25.4 days) returned quicker than did female (35.5 days) and non-intercollegiate (34.7 days) cadets (34).…”
Section: Service Academy Specific Findings To Datementioning
confidence: 91%
See 1 more Smart Citation